The Neuroprotective Effect of Flavonoids in Huntington’s Disease: A Systematic Review - Sang Ayu Arta Suryantari; Anak Agung Intan Pramesti; I Made Suma Wirawan; I Gusti Ngurah Mambal Wirajangsa; I Wayan Yudha Wedantha; Ni Putu Elisya Nathania Fidela (Jurnal Ilmiah Medicamento, 2026)
Background: Huntington’s disease (HD) is a hereditary neurodegenerative disorder characterized by progressive striatal and cortical neuronal loss, resulting in severe motor, cognitive, and psychiatric deficits for which no disease-modifying therapy currently exists. Flavonoids, abundant polyphenolic phytochemicals, are increasingly recognized for their potent neuroprotective properties, specifically acting as antioxidants, anti-inflammatory agents, and modulators of apoptosis and autophagy.Objective: This systematic literature review was conducted to synthesize and critically evaluate contemporary preclinical evidence regarding the efficacy of flavonoids in animal models of HD.Methods: A comprehensive search was executed across PubMed, ScienceDirect, and MEDLINE databases (2015–2025) using specific keyword combinations. Studies investigating flavonoid effects in HD animal models with full-text availability were included, whereas publications older than ten years and review studies were excluded. Methodological quality was assessed using the Joanna Briggs Institute (JBI) critical appraisal tool. Twelve eligible animal studies were identified, demonstrating methodological quality ranging from good to very good.Results: Consistent findings indicated that flavonoid administration significantly enhanced motor coordination and cognitive performance, attenuated oxidative stress and neuroinflammation, and preserved neuronal integrity. These protective outcomes were mediated through the modulation of multiple molecular pathways, encompassing antioxidant defense systems, inflammatory signaling cascades, and apoptosis-related mechanisms.Conclusion: While current preclinical evidence is promising, underscoring the critical roles of flavonoids as multifaceted neuroprotective agents, further rigorously designed clinical trials are imperative to validate these findings and establish the therapeutic potential and clinical applicability of flavonoids for patients suffering from Huntington’s disease.